Comparison of Two Designs of Wireless Electromyography Sensor Module Using Disposable Electrodes and Dry Electrodes in a Sit to Stand Motion - Amrinsani, Farid; Wakidi, Levana Forra; Suryanta, Made Dwi Pandya; Wulandari, Dessy Tri; Caesarendra, Wahyu (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
Electromyography is one of the biosignals used to detect muscle signals in humans. Electromyography signals are widely used as input and are engineered to help people with disabilities or assist them in post-stroke therapy recovery. Based on this phenomenon, a lot of electromyography module sensor designs were made to support various purposes in accordance with research. The purpose of this study was to compare the electromyography sensor module using a disposable electrode and a dry electrode using a wireless serial communication system. The results of this study was based on the experiment carried out in the movement from sitting to standing. Therefore, the difference would be more visible by looking at the Mean Power (MNP) value than the mean frequency (MNF). In this case, the tests were conducted using a disposable electrode, all Bluetooth test distances, relaxed conditions with a mean power value of 0.000453, and contraction with a mean power value of 0.000494. In addition, the researchers also compared serial communication transmissions using cables in relaxed conditions with a mean power value of 0.000460 and contraction with a mean power value of 0.000496. Furthermore, trials were further conducted using dry electrodes, all Bluetooth test distances, relaxed conditions with a mean power value of 0.000455, and contraction with a mean power value of 0.000503. In this case, the researchers compared serial communication transmissions using cables in relaxed conditions with a mean power value of 0.000454 and contraction with a mean power value of 0.000499. It was concluded that the design built and analyzed using mean power (MNP), obtained results that were not much different between electromyography modules using wired and wireless serial communications. It was also obtained that the electromyography module design in this study had no problem with the information.